Activation of aryl hydrocarbon receptor dissociates fatty liver from insulin resistance by inducing fibroblast growth factor 21. Issue 6 (27th February 2015) - Lu, Peipei; Yan, Jiong; Liu, Ke; Garbacz, Wojciech G.; Wang, Pengcheng; Xu, Meishu; Ma, Xiaochao; Xie, Wen
<x xml:space="preserve">Abstract</x> The aryl hydrocarbon receptor (AHR), also known as the dioxin receptor, was originally characterized as a xenobiotic receptor that senses xenotoxicants. We investigated the endobiotic and hepatic role of AHR in fatty liver and energy metabolism and identified the endocrine factor that mediates the metabolic function of AHR. Wild‐type and liver‐specific constitutively activated human AHR transgenic mice were used to investigate the role of AHR in fatty liver and energy homeostasis. Adenovirus expressing short hairpin RNA targeting fibroblast growth factor 21 (FGF21) were used to determine the involvement of FGF21 in the metabolic effect of AHR. We showed that, despite their severe fatty liver, the transgenic mice were protected from diet‐induced obesity and type 2 diabetes. We identified the endocrine hormone FGF21 as a mediator for the metabolic benefit of AHR and established FGF21 as a direct transcriptional target of AHR. Interestingly, the transactivation of FGF21 by AHR contributed to both hepatic steatosis and systemic insulin hypersensitivity, both of which were largely abolished upon FGF21 knockdown. Conclusions: The AHR‐FGF21 endocrine signaling pathway establishes AHR as a pivotal environmental modifier that integrates signals from chemical exposure in the regulation of lipid and energy metabolism. (Hepatology 2015;61:1908–1919)